2017
DOI: 10.12788/jhm.2693
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression in Hospitalized Medical Patients

Abstract: Depression among hospitalized patients is often unrecognized, undiagnosed, and therefore untreated. Little is known about the feasibility of screening for depression during hospitalization, or whether depression is associated with poorer outcomes, longer hospital stays, and higher readmission rates. We searched PubMed and PsycINFO for published, peer-reviewed articles in English (1990English ( -2016 using search terms designed to capture studies that tested the performance of depression screening tools in inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 55 publications
1
26
0
2
Order By: Relevance
“…One study reported a low sensitivity for annual screening in identifying depression among patients with coronary artery disease, which may be true for patients with diabetes as well (Shankman, Nadelson, McGowan, Sovari, & Vidovich, ). Another researcher recommended screening for depression in hospitalized patients with medical illnesses (IsHak et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a low sensitivity for annual screening in identifying depression among patients with coronary artery disease, which may be true for patients with diabetes as well (Shankman, Nadelson, McGowan, Sovari, & Vidovich, ). Another researcher recommended screening for depression in hospitalized patients with medical illnesses (IsHak et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of this study uphold the role of healthcare professionals in recognizing depression in hospitalized patients with diabetes. Any team members can administer a screening questionnaire for depression with the proper training (IsHak et al, ). Nurses, healthcare providers, clinical social workers, case managers, and other professionals directly involved in patient care need ongoing education on the increased risk of depression in patients with diabetes and the warning signs of depression.…”
Section: Discussionmentioning
confidence: 99%
“…31 As such, 3 hospital setting/acute pain guidelines and 3 chronic pain guidelines recommend screening for mental health issues including anxiety and depression. 13,14,16,20,22,23 Several depression screening instruments have been validated among inpatients, 32 and there are validated single-item, self-administered instruments for both depression and anxiety (Table 3). 32,33 Although obtaining a comprehensive history before making treatment decisions is ideal, some patients present in extremis.…”
Section: Obtaining a Comprehensive Pain Historymentioning
confidence: 99%
“…The United States Preventative Services Task Force (USPSTF) recommends depression screening in the general adult population, particularly in pregnant and postpartum women [3]. Screening in hospital settings and medical practices may aid providers in identifying depression; however, screening methods need to be efficiently and feasibly implemented in medical care settings [4,5].…”
Section: Introductionmentioning
confidence: 99%